2020
DOI: 10.1093/jas/skaa182
|View full text |Cite
|
Sign up to set email alerts
|

Replacing cottonseed meal and sorghum grain with corn dried distillers’ grains with solubles in lamb feedlot diets: carcass, trained sensory panel, and volatile aroma compounds traits

Abstract: In a randomized design study, lambs were individually fed with ad libitum access to 70.9% concentrate diets for 56-d in individual pens. The positive control diet (CNTL) contained cotton seed meal (CSM), sorghum grain, and cotton seed hulls, but no DDGS. Four treatment diets were similar to CNTL but did not contain CSM. Corn DDGS replaced 0% (0DDGS), 33% (33DDGS), 66% (66DDGS) or 100% (100DDGS) of the sorghum grain in the treatment diets. At 48-h postmortem, the longissimus muscle (LM) was removed from the car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
2
8
0
1
Order By: Relevance
“…Increasing the DDGS levels in the diets quadratically increased shrunk BW ( P = 0.03) and HCW ( P = 0.02; Table 5 ), corroborating with Hodges et al (2020b) who tested replacing CMS and SG with DDGS in feedlot Dorper intact male lamb diets.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Increasing the DDGS levels in the diets quadratically increased shrunk BW ( P = 0.03) and HCW ( P = 0.02; Table 5 ), corroborating with Hodges et al (2020b) who tested replacing CMS and SG with DDGS in feedlot Dorper intact male lamb diets.…”
Section: Resultssupporting
confidence: 75%
“…Increasing the DDGS levels in the diets quadratically increased the initial and sustained juiciness ( P < 0.02) and tenderness ( P < 0.009). According to Hodges et al (2020b) , although the addition of DDGS to feedlot lamb diets did not affect muscle fiber tenderness and connective tissue amount, it linearly increased meat tenderness. The increase of carcass backfat thickness and body wall from lambs fed with 25DDGS and 50DDGS may have reduced cold shortening ( Smith and Carpenter, 1973 ) and its effects on decreasing sarcomere length and increasing shear force ( Aalhus et al, 2001 ; Okeudo and Moss, 2005 ), which can be perceived by sensory panelists ( Destefanis et al, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, phytol was found in a greater amount in loin fat of a clover-finished lamb than in that of a maize-finished lamb [ 44 ]. Trimethylpyrazine has been well described in lamb meat [ 45 , 46 ], but it seems not to be related to diet characteristics [ 16 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Protein and amino acid utilization of corn dried distillers grains has been evaluated in growing lambs and the results indicated that this by-product represents an excellent source of protein (Archibeque et al, 2008). Moreover, the high supply and corn price has made dried corn distillers grains a very attractive source of energy for ruminants (Klopfenstein et al, 2008;Hodges et al, 2020).…”
Section: Introductionmentioning
confidence: 99%